Limbo or Leverage? Asylum waiting and refugee integration - Olof Aslund; Olof Rosenqvist (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
We study the impact of asylum waiting, exploiting a rapid increase in processing times for asylum seekers to Sweden. Longer waiting slows down integration. Accumulated earnings during the first four years after application are 2.3 percent lower per added month of waiting. The impact is due to delay rather than negative effects of waiting per se. There is no evidence of detrimental effects on psychiatric or other forms of health. From the date of asylum, those who have waited longer perform better in the labor market and are more likely to start advanced language training and labor market programs.
Keywords: F22; J15; J68; 330; Asylum waiting; labor market; health